The Role of the Kediri Police Satbinmas Binkamsa Unit Through Sambang Satkamling in Preventing the Crime of Theft with Aggravating Circumstances - Reza, Muhamad cecep (Advances in Police Science Research Journal, 2024)
The increase in criminal activities in 2022 at the Kediri Police Resort, especially in cases of aggravated theft, has risen from 2020 to 2022. Therefore, this research aims to describe the role of the Unitbinkamsa in preventing aggravated theft crimes, identify the factors influencing the implementation of Satkamling patrols in preventing aggravated theft crimes, and assess the efforts made by the Unitbinkamsa in the Kediri Police Resort. This research adopts a qualitative approach with data collection through interviews, and the applied theories include Crime Prevention, Management, and Communication. The conceptual focus encompasses the roles and functions of Unitbinkamsa, Satkamling patrols, and aggravated theft. The research findings indicate the role of Unitbinkamsa as a mediator in resolving social issues within the community, with internal and external factors affecting police officers in their efforts to prevent such criminal activities.